Student Services Center (SSC): Upaya pembinaan prestasi, karir, dan kewirausahaan bagi mahasiswa melalui community based participatory research - Anwar, Saiful (Penamas: Journal of Community Service, 2021)
The purpose of this service is to develop academic competence, non-academic competence, entrepreneurial competence and prepare the careers of students and alumni of the Islamic Economics and Business Faculty IAIN Salatiga. The service is carried out using a Community Based Participatory Research (CBPR) approach. Laying foundation is done by analyzing the situation, reasons for choosing partners, conditions of assistance. partner engagement plans, and framing research questions for action plans. The tools used are community mapping in the hope of capturing the strengths, potentials, and issues that exist among students. Action plans carried out by establishing the Students Service Center (SSC), Launching Students Service Center (SSC), developing student academic competencies through presentation skill training, debate competition mentoring/coaching, business plan mentoring/coaching, training in writing scientific papers, developing non-technical competencies student academics through futsal day and volleyball day, developing student entrepreneurship potential by mentoring millennial entrepreneurs, entrepreneurship talk shows, halal food festivals, student career development through advanced study seminars, scholarship interview mentoring, leadership talk shows, work simulations. The contribution of this research creates social changes in the research process and meaningful results that can improve campus reputation through student achievement